Antidiarrheal and Antioxidant Activities of Methanol Extract of Bryophyllum pinnatum Leaf Harvested from South-Eastern Nigeria in Mice. (29th May 2018) - Onoja, Samuel O.; Ihejirika, Ginika Q.; Nwankudu, Oluchi N.; Omeh, Yusuf N.; Ezeja, Maxwell I.
Abstract : Bryophyllum pinnatum belongs to the family Crassulaceae and it is commonly used in the ethnomedical practices. This study investigated the antidiarrheal and antioxidant properties of methanol extract of Bryophyllum pinnatum leaf harvested from South-Eastern Nigeria in mice. Cold maceration method in 80% methanol was adopted in the extract preparation. The 2, 2-diphenyl-1-picrylhydrazyl (DPPH) and ferric reducing antioxidant power (FRAP) assays were used to evaluate the antioxidant property while castor oil-induced diarrhea, small intestinal transit, and enteropooling models were used for the antidiarrheal investigation. The effects of the extract (50, 100, and 200 mg/kg) were compared to distilled water (10 ml/kg) and loperamide (5 mg/kg). The extract produced concentration dependent increase in antioxidant effect in both DPPH and FRAP assay. The extract caused a significant (p < 0.05 ) reduction in mean stool output, percentage of wet stools, small intestinal transit, and intestinal fluid accumulation in the treated mice when compared to the distilled water treated mice. The study validates the use of Bryophyllum pinnatum in the ethnomedical management of diarrhea.